2023
DOI: 10.3390/vaccines11061096
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Intentions, Concerns and Information Needs about COVID-19 Vaccination in New Jersey: A Qualitative Analysis

Abstract: Background: In 2019, the World Health Organization identified vaccine hesitancy as a top ten global health threat, which has been exacerbated by the COVID-19 pandemic. Despite local and nationwide public health efforts, adolescent COVID-19 vaccination uptake in the US remains low. This study explored parents’ perceptions of the COVID-19 vaccine and factors influencing hesitancy to inform future outreach and education campaigns. Methods: We conducted two rounds of individual interviews via Zoom in May–September… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(63 reference statements)
1
1
0
Order By: Relevance
“…Similar to what has been previously reported, 33 we found parents used a variety of sources to obtain information about COVID-19, and often sought information online (Google search, YouTube, government websites). However, parents mentioned the need for simple, evidence-based knowledge mobilisation products (easily accessible, preferably online resources) to support their informed decision making.…”
Section: Information Needssupporting
confidence: 79%
See 1 more Smart Citation
“…Similar to what has been previously reported, 33 we found parents used a variety of sources to obtain information about COVID-19, and often sought information online (Google search, YouTube, government websites). However, parents mentioned the need for simple, evidence-based knowledge mobilisation products (easily accessible, preferably online resources) to support their informed decision making.…”
Section: Information Needssupporting
confidence: 79%
“…Similar to recent findings by Kohler et al, parents were frustrated with the lack of clear communication, and how policies seemed to change so frequently regarding public health measures. 33 Parents expressed feeling overwhelmed with the amount of information available online, particularly regarding COVID-19 vaccinations and isolation requirements. 7,8 Though many participants believed available COVID-19 vaccinations were safe for adults and revealed that they themselves were vaccinated, others questioned vaccine safety with young children and the necessity of getting vaccinated if children had already been infected.…”
Section: Parent Experiencesmentioning
confidence: 99%